ACCRUAL DAN REAL EARNING MANAGEMENT DALAM MERESPON PENURUNAN TARIF PAJAK PENGHASILAN BADAN TAHUN 2010 - Setiadi Alim Lim (University of Merdeka Malang, 2013)
Research conducted by Guenther (1994) shows the behavior of management to conduct income decreasingearning management in the period of one year before the income tax rate reduction in order to obtain relief theburden of income tax paid. The research of Alim (2009) showed indications of income decreasing earningmanagement in the 2008 financial statements of business entities in Indonesia Stock Exchange responding toa decrease in income tax corporate tax-payers in 2009. This study aimed to investigate whether there is anindication of income decreasing earning management and also on the 2009 financial statements of businessentities in Indonesia Stock Exchange responding to reduced income tax rate for corporate tax-payers in 2010.To detect the presence of income decreasing earning management variables to discretionary accruals will beused to indicate the presence of accrual/accounting earnings management and abnormal variable cash flowsfrom operations and abnormal discretionary expenses that may indicate the presence of real earning management.The results showed an indication of income decreasing earning management is detected through avariable discretionary accruals and abnormal cash flow from operations but not found through variableabnormal discretionary expenses.